The glutamate/aspartate transporter EAAT1 is crucial for T-cell acute lymphoblastic leukemia proliferation and survival - Stanulović, Vesna S.; Al Omair, Shorog; Reed, Michelle A.C.; Roberts, Jennie; Potluri, Sandeep; Fulton-Ward, Taylor; Gudgeon, Nancy; Bishop, Emma L.; Roels, Juliette; Perry, Tracey A.; Sarkar, Sovan; Pratt, Guy; et al. (Haematologica (Roma), 2024)
T-cell acute lymphoblastic leukemia (T-ALL) is a cancer of the immune system. Approximately 20% of paediatric and 50% of adult T-ALL patients have refractory disease or relapse and die from the disease. To improve patient outcome new therapeutics are needed. With the aim to identify new therapeutic targets, we combined the analysis of T-ALL gene expression and metabolism to identify the metabolic adaptations that T-ALL cells exhibit. We found that glutamine uptake is essential for T-ALL proliferation. Isotope tracing experiments showed that glutamine fuels aspartate synthesis through the TCA cycle and that glutamine and glutamine-derived aspartate together supply three nitrogen atoms in purines and all but one atom in pyrimidine rings. We show that the glutamate-aspartate transporter EAAT1 (SLC1A3), which is normally expressed in the central nervous system, is crucial for glutamine conversion to aspartate and nucleotides and that T-ALL cell proliferation depends on EAAT1 function. Through this work, we identify EAAT1 as a novel therapeutic target for T-ALL treatment.